THE ASSOCIATION BETWEEN MATERNAL CHARACTERISTICS AND COMPLETENESS OF BASIC IMMUNIZATION SERIES AMONG TODDLERS IN KOTA AND JAMBULA PUBLIC HEALTH CENTERS IN TERNATE - Azril Azril; Fera The; Abdul Hakim Husen (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2022)
Background: Immunization is the process of developing immunity towards against infectious diseases through vaccination.  In 2019, the highest and lowest complete basic immunization coverage were achieved in Jambula (100%) and Kota (89%) public health centers, respectively.  Maternal characteristics are considered to play role in basic immunization coverage among toddlers. Purpose: To identify the association between maternal characteristics and completeness of basic immunization among toddlers in the Kota and Jambula public health centers, Ternate. Method: Using purposive sampling, this analytical observational study was conducted in the Kota and Jambula public health centers, Ternate, in 2021. Results: From 192 samples, statistically significant associations were identified between maternal education, knowledge, and attitudes, with the completeness of basic immunizations (p<0,05). No significant associations were detected with maternal age and maternal work. Conclusions: Maternal education, knowledge, and attitudes may affect the completeness of basic immunizations among toddlers. The need for sound programs and parental education regarding complete basic immunizations among toddlers might be crucial.Keywords: immunization, maternal characteristics, Kota Public Health Center, Jambula Public Health Center